Adsorption studies of graphene oxide for lead removal from synthetic wastewater - Nik Abdul Ghani, Nik Rashida; Jami, Mohammed Saedi; Ku Abdullah, Ku Mariam Zainab (IIUM Press, 2019)
Lead contamination present in wastewater is one of the major problems due to its toxicity and persistence. This issue increased dramatically and led to the environmental and health concerns worldwide. Therefore, this study aims to remove lead from synthetic wastewater effluent by adsorption process. In this study, nanomaterial called graphene oxide (GO) is used as an adsorbent due to its mechanical strength and high surface area. The parameters were optimized using Fractional factorial design under response surface method. GO demonstrates high adsorption capacity, qmax = 500 mg/g at 100 mg/L of initial lead concentration and at optimum pH 9. Adsorption isotherm of lead was also investigated to evaluate the adsorption capacity. The equilibrium data of graphene oxide adsorption was better represented by the Langmuir isotherm and was achieved within 60 minutes. The results showed that GO has potential to be an important adsorbent for lead removal. In the future, GO might be imbedded as adsorbent in the membrane fabrication for wastewater treatment.